Other targeted drugs in melanoma - González-Cao, María; Rodón, Jordi; Karachaliou, Niki; Sánchez, Jesús; Santarpia, Mariacarmela; Viteri, Santiago; Pilotto, Sara; Teixidó, Cristina; Riso, Aldo; Rosell, Rafael (Annals of Translational Medicine; Vol 3, No 18 (October 30, 2015): Annals of Translational Medicine (Focus on “Melanoma”), 2015)
Targeted therapy drugs are developed against specific molecular alterations on cancer cells. Because they are “targeted” to the tumor, these therapies are more effective and better tolerated than conventional therapies such as chemotherapy. In the last decade, great advances have been made in understanding of melanoma biology and identification of molecular mechanisms involved in malignant transformation of cells. The identification of oncogenic mutated kinases involved in this process provides an opportunity for development of new target therapies. The dependence of melanoma on BRAF-mutant kinase has provided an opportunity for development of mutation-specific inhibitors with high activity and excellent tolerance that are now being used in clinical practice. This marked a new era in the treatment of metastatic melanoma and much research is now ongoing to identify other “druggable” kinases and transduction signaling networking. It is expected that in the near future the spectrum of target drugs for melanoma treatment will increase. Herein, we review the most relevant potential novel drugs for melanoma treatment based on preclinical data and the results of early clinical trials.